SOIL TILLAGE SYSTEM AND PRECROPS INFLUENCE ON SPRING WHEAT FLAG LEAF AREA AND GRAIN QUALITY INDICATORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Spring wheat (Triticum aestivum L.) is the most widely grown spring cereal in Latvia. The aim of the research was to determine soil tillage system and precrops influence of spring wheat flag leaf area and grain yield quality indicators. Field trials were carried out at the Research and Study farm “Peterlauki” study site “Poki” (56º30.658’ N and 23º41.580’ E) of the Latvia University of Life Sciences and Technologies (LBTU) at year 2024. Spring wheat ‘Berlock’ was grown with two soil tillage systems (conventional and minimal soil tillage) and three different precrops (winter wheat, winter oilseed and spring oilseed rape). The flag leaf area (cm2) has been analyzed by using scanner STD4800 and specialized computer software WinFOLIA. The determination of the yield components, grain yield (t ha-1) and straw yield (t ha-1) was made by sample sheaf analysis. Grain quality indicators: crude protein content; starch content; gluten content and Zeleny index, thousand grain weight were determined in Grain and seed study and research laboratory at LBTU. Significant differences (p<0.05) between soil tillage systems were found in flag leaf area and length. A strong positive correlation was observed between grain yield and flag leaf area r=0.854 for conventional and r=0.958 for minimal soil tillage system. Sample sheaf analysis showed significant differences in spike mass and grain weight. Among grain quality indicators, gluten content differed significantly and significant differences were associated with the precrops (p<0.05). It should be noted that in the 2024 growing season, July saw increased precipitations at the trial site.